Protein phosphatase 2A regulatory subunits perform distinct functional roles in the maize pathogen Fusarium verticillioides. (3rd March 2013) - Shin, Joon‐Hee; Kim, Jung‐Eun; Malapi‐Wight, Martha; Choi, Yoon‐E.; Shaw, Brian D.; Shim, Won‐Bo
Summary Fusarium verticillioides is a pathogen of maize causing ear rot and stalk rot. The fungus also produces fumonisins, a group of mycotoxins linked to disorders in animals and humans. A cluster of genes, designated FUM genes, plays a key role in the synthesis of fumonisins. However, our understanding of the regulatory mechanism of fumonisin biosynthesis is still incomplete. We have demonstrated previously that Cpp1, a protein phosphatase type 2A (PP2A) catalytic subunit, negatively regulates fumonisin production and is involved in cell shape maintenance. In general, three PP2A subunits, structural A, regulatory B and catalytic C, make up a heterotrimer complex to perform regulatory functions. Significantly, we identified two PP2A regulatory subunits in the F. verticillioides genome, Ppr1 and Ppr2, which are homologous to Saccharomyces cerevisiae Cdc55 and Rts1, respectively. In this study, we hypothesized that Ppr1 and Ppr2 are involved in the regulation of fumonisin biosynthesis and/or cell development in F. verticillioides, and generated a series of mutants to determine the functional role of Ppr1 and Ppr2. The PPR1 deletion strain (Δppr1) resulted in drastic growth defects, but increased microconidia production. The PPR2 deletion mutant strain (Δppr2) showed elevated fumonisin production, similar to the Δcpp1 strain. Germinating Δppr1 conidia formed abnormally swollen cells with a central septation site, whereas Δppr2 showed early hyphal branching during conidia germination. A kernel rot assay showed that the mutants were slow to colonize kernels, but this is probably a result of growth defects rather than a virulence defect. Results from this study suggest that two PP2A regulatory subunits in F. verticillioides carry out distinct roles in the regulation of fumonisin biosynthesis and fungal development.